Utilization of Contextual-Based Student Worksheets (LKPD) to Improve Mathematics Literacy of MTs N 3 Jombang Students - Nuril Huda; Muhammad Al Farabi (Southeast Asian Mathematics Education Journal, 2026)
Mathematical literacy remains a persistent challenge in Indonesian education, as highlighted by the 2022 PISA report. Preliminary assessment results showed that most students (82.14%) at an Islamic junior high school had not yet achieved a good level of mathematical literacy. This study aims to examine the utilization of contextual-based worksheets (LKPDs) that integrate mathematical problem-solving with Islamic values and daily religious practices to improve students’ mathematical literacy skills. The study employed a Classroom Action Research (CAR) design involving 28 eighth-grade students at a State Islamic Junior High School. The participants, aged between 13 and 14 years old, were selected because preliminary observations showed that their mathematical literacy skills were mostly at a sufficient or low level. Data were collected through tests, interviews, and documentation. Research data were analysed using qualitative-descriptive method. The findings revealed a significant improvement in students mathematical literacy skills, as indicated by the percentage of students achieving at least a 'good' level of mathematical literacy: 17,86% in the preliminary stage, 39,29% in Cycle I, and 78,57% in Cycle II. These findings suggest that the utilization of contextual-based worksheets effectively improves the mathematical literacy skills of Islamic junior high school students.